Determinación de hemoglobina y hematocrito en personas adultas de ambos sexos en el sector Los Huertos Virgen del Socorro, distrito de Huanchaco – julio 2014. - Rodríguez Garcia, Anita Milady (2014)
The present research aimed to determine the level of hemoglobin and hematocrit in adults of both sexes in the field "The Gardens Virgen del Socorro" district Huanchaco - July 2014, prior informed consent, samples and respective determinations were made a total of 82 people, 39% male and 61% female. Hemoglobin levels of 2.44% were found in a high range, the 79.27% of the participants were within normal and decreased 18.29% and about 6.1% hematocrit were found in a high range, the normal 54.88%, and 39.02%, lower levels. The relationship between the variables, using the Chi square test revealed that there is no significant relationship between eating habits and the level of hematocrit (p> 0.05), however if they showed the existence of relationship with hemoglobin levels (p <0.05 ). It is concluded that hemoglobin levels are influenced by the variety in food consumption, and improper use of them can lead to a picture of iron deficiency anemia